The surface chemistry of polystyrene latices initiated by the persulfate/bisulfite/iron system - McCarvill, William T; Fitch, Robert M (Journal of colloid and interface science, 1978)
A series of polystyrene colloids in water was prepared by emulsion polymerization using the PBI initiator system [persulfate/bisulfite/iron (III)] and SDS surfactant (sodium dodecyl sulfate). In one case no surfactant was used. In some, divinyl benzene was employed as a crosslinking agent. The colloids were purified and converted to the surface acid form by a combination of continuous hollow fiber dialysis and ion exchange. The kinetics of the autocatalyzed hydrolysis of certain surface acid groups, presumably RSO 4H, were determined at 70, 86, and 100°C by conductometric titration. Hydrolysis also occurred during dialysis and ion exchange. A residuum of nonhydrolyzable surface acid, presumably RSO 3H, was always found. Mixed bed ion-exchange resins could be used to clean the colloids only after exhaustive purification, even though separate cation and anion resins appeared always to contaminate the latex surface. Dialysis alone was unsatisfactory.